Evaluation of the high-temperature rheological performance of tire pyrolysis oil-modified bio-asphalt - Al-Sabaeei, A.M. (Taylor and Francis Ltd., 2021)
This study seeks to examine the physical and high-temperature rheological performance of crude palm oil (CPO)/tire pyrolysis oil (TPO) composite asphalt to develop a more sustainable bio-rubberized asphalt (BRA) binder. The study uses the penetration, softening point, and dynamic viscosity tests to evaluate binder consistency and dynamic shear rheometer (DSR) tests to determine the linear viscoelastic properties before and after short-term aging. The nonlinear viscoelastic properties of modified asphalt were determined using the multiple stress creep recovery (MSCR) test. Results showed that the substitution of 20 asphalt with tire pyrolysis oil-modified bio-asphalt retained or enhanced the asphalt grade performance at high temperatures. All BRA binders have a higher aging resistance than the base asphalt. The MSCR results showed that, relative to all tested binders, the BRA binder containing 5 CPO and 5 TPO has optimal non-recoverable creep compliance (Jnr) and percentage of recovery (R) with a performance close to PG64H compared to the PG64S performance grade of the base asphalt. Overall, the findings of this study indicate that the incorporation of CPO/TPO in asphalt is suitable for producing bio-rubberized asphalt containing 20 recycled waste rubber and bio-oil and improves the high-temperature properties of asphalt to a certain extent. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.